Communication Case Studies for Health Care Professionals : an Applied Approach. - Pagano, Michael P. (Springer Publishing, 2014)
Praise for the first edition:. "". . . allows students and faculty to explore real-life health communication behaviors through role-playing, interactive exercises, and examples ... easily adapted for use in many situations, sensitivity and diversity training ... very worthwhile book for every medical faculty member working to instill professionalism ... in students.""--Vincent Carr, DO, MSA, FACC, FACP. Uniformed Services University of the Health Sciences. The importance of good communication between health professionals and patients has been well documented. Not only does it foster page.